Pheomelanogenesis is promoted at a weakly acidic pH. (22nd April 2017) - Wakamatsu, Kazumasa; Nagao, Ayano; Watanabe, Miu; Nakao, Kenta; Ito, Shosuke
Summary: The diversity of pigmentation in the skin, hair, and eyes of humans has been largely attributed to the diversity of pH in melanosomes with an acidic pH being proposed to suppress melanin production, especially eumelanogenesis. We previously showed that an acidic pH greatly suppresses the late stage of eumelanogenesis after the dopachrome stage. The oxidation of tyrosine by tyrosinase in the presence of cysteine forms cysteinyldopa isomers, which are further oxidized to give rise to pheomelanin via benzothiazine intermediates. However, how those steps are controlled by pH has not been characterized. We therefore examined whether pheomelanin synthesis is chemically promoted at an acidic pH. We found that pheomelanin production either from dopa or tyrosine in the presence of cysteine by tyrosinase was greatest at pH values of 5.8–6.3, while eumelanin production was suppressed at pH 5.8. This suggests that mixed melanogenesis is chemically shifted to more pheomelanic states at a weakly acidic pH.